CoMa-mSCTP: a connectivity management scheme based on mSCTP in mobile environments - SHI Yan1; CHEN Shan-zhi2; DONG De-cai1; LI Yu-hong1 (Tongxin xuebao)
An mSCTP-based connectivity management scheme,CoMa-mSCTP,was proposed to realize the integration of bandwidth aggregation and mobility supporting at transport layer.The major path management functions were defined and the path handoff procedure was introduced.A transport path subset selection policy based on wide-sense path defini-tion was proposed.The simulations on the effect of the throughput improvement,the path subset selection policy and the mobility supporting were complemented respectively.The simulation results show that CoMa-mSCTP can realize effi-cient integration of bandwidth aggregation and mobility and the application-based path subset selection policy has ap-parent performance advantages.